Demokratisasi Pengelolaan Zakat Melalui Perubahan Peran Lembaga Amil Zakat berbasis Organisasi Kemasyarakatan - Dwi Martiningsih; Arif Zamhari (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2021)
The management of zakat is dynamic dealing with the socio-political context in a country, including Indonesia. Zakat regulation  change from UU/38/1999 to UU/23/2011 pratically require adaptation from the role of zakat institutions in Indonesia. Zakat management institution in the community such as NU-Care LAZISNU and LAZISMU as zakat management institutions with civil society-based in programs and activities certainly cannot be separated from these regulatory changes. The regulation change was responded by changing its role as a zakat management institution. This article aims to describe the activities of NU-Care LAZISNU and LAZISMU and their position in responding zakat law. This research uses a case study approach and is designed in the form of a descriptive analysis to reveal field findings. The results of this research reveal that changes in national zakat management bring opportunities as well as challenges for zakat management institutions, both government zakat institutions and non-government zakat institutions. NU-care LAZISNU and LAZISMU build some adjustments by modernizing their institutions. These two civil society-based zakat institutions carry out various strategies in collecting, distributing and empowering zakat, infaq, and sedekah.